Social media optimization as an advertising tool for business development - Nugrahaning Esa Pratiwi; Johannes Latuny; Big Greogory Kaitelapatay (Jurnal Mantik, 2023)
Having a business requires the ability to manage and develop it and the way is from advertising. Interesting and popular advertising today is to optimize new media, that is social media. My Rise as a small fashion business in Salatiga city, initiated by young people who know the importance of social media and can manage and utilize social media, brought My Rise can survive until this day. Through a qualitative descriptive approach, research data obtained from interviews and observations on My Rise's social media were analyzed to get the answer of research questions about social media optimization as an advertising tool for business development at My Rise. The result shows that My Rise uses social media including Facebook, Instagram and TikTok where the advertising content displayed is in audio, video, and photos while using the features offered and adjusting the audience's character. In the other way, My Rise continues to manage its offline store and participate in weekly traditional market events as personal branding. Social media optimization as an advertising tool has positively impacted My Rise, namely increasing the number of customers and income.%MCEPASTEBIN%